Arthroscopic anatomical reconstruction of the lateral collateral ankle ligament: an examination of the learning curve and the influence of laterality and body mass index. (26th February 2021) - Courtine, Matthieu; Tomes, Sébastien; Molinier, François; Cellier, Nicolas; Bauer, Thomas
Objectives: Anatomical reconstruction under arthroscopy by gracilis tendon autograft is an innovative technique in full development and requires a learning curve. Our objective was to evaluate this curve and determine the influence of the surgical side and the patient's body mass index (BMI) on the performance of the procedure. Methods: In this retrospective study, conducted from January 2015 to March 2020, data was collected from 7 centers through 11 operators, and included the surgical side, body mass index and total procedure time. The ankle ligament reconstruction had to be performed entirely under arthroscopy, without any associated procedure, at the expense of the gracilis tendon. The learning curve was calculated over the total operating time. Results: The learning curve showed a logarithmic pattern with an average decrease of 20% in operating time for the 4th patient. In the largest cohort, there was a significant difference in operating time between the right and left sides (35.39 minutes vs. 32.29 minutes, p < 0.002, [CI95] = 1.23; 4.98). In the two largest cohorts, there was a correlation between operating time and BMI (ρ= 0.7022, p < 7.29E-20, [CI95] = 0.6006; 0.7814 and ρ= 0.2749, p < 0.025, [CI95] = 0.0371; 0.4832) for all the patients (ρ= 0.1753, p < 0.0001, [CI95] = 0.0867; 0.2612). Conclusion: Arthroscopic anatomical ligament reconstruction of the ATFL and CFL is a technical intervention with a fast learning curve, with good control of the procedure in less than ten procedures. The surgical side and the patient's BMI were noted to have an influence on the duration of the procedure.